Epoxy resin nanocomposites with hydroxyl (OH) and amino (NH2) functionalized boron nitride nanotubes. Issue 1 (2nd January 2018) - Guan, Jingwen; Ashrafi, Behnam; Martinez-Rubi, Yadienka; Jakubinek, Michael B.; Rahmat, Meysam; Kim, Keun Su; Simard, Benoit
Abstract: Hydroxyl (OH) and amino (NH2 ) functionalized boron nitride nanotubes (f-BNNTs) were integrated into an epoxy resin (Epon828) to achieve improved mechanical properties. While raw BNNT-composites yielded the largest values for Young's modulus and appeared to be well mixed, f-BNNTs were found to provide a superior combination of mechanical properties yielding improvements in strain at failure, tensile strength and toughness that were not observed using raw BNNTs. In particular, an increase of 21% in Young's modulus is observed with 5 wt% of f-BNNT, and increases of 12, 21, and 49% are observed in tensile strength, failure strain, and toughness, respectively, with 2 wt% f-BNNT while a 34% increase in fracture toughness is observed with 3 wt% f-BNNT. Abstract :